Dietary advice both significantly reduces colitis disease activity, steroid requirement and increases quality of life in patients with ulcerative colitis. (13th March 2011) - Kyaw, M; Moshkovska, T; Bagewadi, A; Mayberry, J
Abstract : Introduction: The impact of food on the relapse of Ulcerative Colitis (UC) has not been clearly defined. Given the mixture of results from previous studies, patients with UC are confused about the role dietary factors may play in their disease. The purpose of this study is to investigate the effect dietary advice on Quality of Life in patients with UC and their disease activity. Methods: 66 patients were randomly allocated to a treatment group and a control group. Patients in the treatment group were given dietary advice via booklet ('Diet and Ulcerative Colitis'). Patient in the control group were given a general dietary booklet, which is normally used to give dietary advice to general public ('Healthy Eating for a Healthy Leicestershire'). Patients were asked to complete IBDQ (Inflammatory Bowel Disease Questionnaire) and SCCAI (Simple Clinical Colitis Activity Index) together with the food frequency questionnaire at 0 week, 6 weeks and 32 weeks. IBDQ, SCCAI, food frequency questionnaires were used to compare patients perceived quality of life, colitis activity scores and eating habits, prior to and following dietary advice given. Results: In the treatment group there were a smaller number of patients that required steroids compared to control group (5.5% vs 20.9%). There was a mean reduction in SCCAI score in the treatment group compared to an increase in the score in the control group (mean differences of −1.30 (p= 0.0108) vs 0.88 (p = 0.0249)). There was a mean increase in IBDQ score in the treatment group compared to a reduction in the score in the control group (mean differences of 7.1 (p=0.12) verses –3.4 (p=0.20)). 69 % of patients in the treatment group found the dietary advice significantly or moderately helpful. Conclusion: Dietary advice reduces the number of patients requiring steroids compared to controls. There is improvement in SCCAI score and Quality of Life in those offered dietary advice. These findings require validation with further larger cohort of patients.